Commutativity Theorems for *-Prime Rings with Differential Identities on Jordan Ideals. (16th December 2012) - Mamouni, A.; Oukhtite, L.; Samman, M.
Abstract : In this paper we explore commutativity of* -prime rings in which derivations satisfy certain differential identities on Jordan ideals. Furthermore, examples are given to demonstrate that our results cannot be extended to semiprime rings.